2022
DOI: 10.1111/cge.14268
|View full text |Cite
|
Sign up to set email alerts
|

Identification of nonfunctional SPATA20 causing acephalic spermatozoa syndrome in humans

Abstract: Acephalic spermatozoa syndrome (ASS) is a rare and severe type of teratozoospermia characterized by the predominance of headless spermatozoa in the ejaculate. However, knowledge about the causative genes associated with ASS in humans is limited. Loss‐of‐function of SPATA20 has been suggested to result in the separation of the sperm head and flagellum in mice, whereas there have been no cases reporting SPATA20 variants leading to human male infertility. In this study, a nonsense mutation in SPATA20 (c.619C > T,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…4 Last, Wang et al suggested that patients with SPATA20 mutations might have poor ICSI outcomes. 1 In our present case, ICSI were also unsuccessful to circumvent infertility in the couple despite two ICSI cycles and three embryos transferred (female partner age = 26) supporting the assumption that ICSI does not seem to be a valuable therapeutic option; however, due to the limited number of studies, it remains difficult to definitively conclude.…”
Section: Dear Editormentioning
confidence: 52%
See 1 more Smart Citation
“…4 Last, Wang et al suggested that patients with SPATA20 mutations might have poor ICSI outcomes. 1 In our present case, ICSI were also unsuccessful to circumvent infertility in the couple despite two ICSI cycles and three embryos transferred (female partner age = 26) supporting the assumption that ICSI does not seem to be a valuable therapeutic option; however, due to the limited number of studies, it remains difficult to definitively conclude.…”
Section: Dear Editormentioning
confidence: 52%
“…We have read with a great interest the article by Wang et al 1 which suggest that biallelic loss-of-functions mutations may lead to male infertility related to acephalic spermatozoa syndrome (ASS). We describe here an infertile patient carrying a novel homozygous truncating variant in SPATA20 (c.1957 + 2 T > A) (Figure 1).…”
Section: Dear Editormentioning
confidence: 99%
“…In fact, male fertility and fertilization require evasion from the own immune response and the one of the partner 99,105 . Still, corresponding GO groups contained genes encoding proteins with clear fertility relevance, such as SPATA20, 11,106 ZPBP, 107 and SPAG4 108 (Table S3). Thus, reference to the immune system should not be overestimated in our opinion.…”
Section: Discussionmentioning
confidence: 99%
“…For expressional topologies of all genes with proteins in Tables 1, 3, and 5, see Figures S1-S3. SPATA20, 11,106 ZPBP, 107 and SPAG4 108 (Table S3). Thus, reference to the immune system should not be overestimated in our opinion.…”
Section: The Human Sperm Proteome and Its Coding Genesmentioning
confidence: 99%
“…The failure of HTCA assembly results in the separation of sperm head from sperm tail, rendering acephalic spermatozoa syndrome (ASS) and male infertility (Hetherington et al, 2016 ; Kim et al, 2018 ; Wang et al, 2022b ; Zhu et al, 2018 ; Zhu et al, 2016 ). ASS refers to sperm in the semen with intact flagella but without sperm head (Wang et al, 2023 ; Yuan et al, 2015 ). In 2015, we first reported that genetic ablation of SPATA6 in mice could result in sperm connecting piece structure disassembly and eventually cause ASS (Yuan et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%